Population Dynamics of Senegal - National Research Council (The National Academies Press, 1995)
This volume, the last in the series Population Dynamics of Sub-Saharan Africa, examines key demographic changes in Senegal over the past several decades. It analyzes the changes in fertility and their causes, with comparisons to other sub-Saharan countries. It also analyzes the causes and patterns of declines in mortality, focusing particularly on rural and urban differences.
Keywords: Behavioral and Social Sciences; Health and Medicine

Careers in Science and Technology: An International Perspective - National Research Council (The National Academies Press, 1995)
Every industrialized country is concerned with maintaining an adequate supply of individuals interested in careers in science and technology, yet little is known about these efforts outside national borders. This book represents the proceedings of an international conference on Trends in Science and Technology Careers, held in Brussels in 1993. Organized at the behest of OSEP and the OIA Committee on International Organizations and Programs, in cooperation with the European Commission (DG XII) and in response to a resolution of the International Council of Scientific Unions, the conference identified international data on career trends, assessed the research base engaged in studying science and technology careers, and identified ways in which international organizations could promote greater interest in science and technology human resource development. The conference laid the groundwork for continuing international discussions about the best ways to study and promote careers in science and technology and national dialogues about the ways to integrate this knowledge into human resources policies.
Keywords: Policy for Science and Technology; Engineering and Technology

Health Consequences of Service During the Persian Gulf War: Initial Findings and Recommendations for Immediate Action - Institute of Medicine (The National Academies Press, 1995)
This initial volume in an ongoing study of the potential health consequences of service during the Persian Gulf War responds to a request from Congress to determine whether actions taken to evaluate health effects have been appropriate. It reflects the committee's examination of health outcomes and related research efforts, women's health and reproductive health issues, infrastructure and procedures for data collection, health services influences, the role of psychiatric diagnosis, and a review of the activities of boards and coordinating groups, as well as how issues stemming from involvement in the Persian Gulf might be relevant for possible future conflicts. While the committee continues its full-length study of the problem, the recommendations in this volume are for actions it feels should be taken immediately.
Keywords: Health and Medicine

Biographical Memoirs: Volume 68 - National Academy of Sciences (The National Academies Press, 1995)
Biographic Memoirs: Volume 68 contains the biographies of deceased members of the National Academy of Sciences and bibliographies of their published works. Each biographical essay was written by a member of the Academy familiar with the professional career of the deceased. For historical and bibliographical purposes, these volumes are worth returning to time and again.
Keywords: Biography and Autobiography

A Miracle and a Privilege: Recounting a Half Century of Surgical Advance - Moore, Francis D. (The National Academies Press, 1995)
Francis Moore entered Harvard Medical School in September of 1935, seven years before penicillin became available. During his remarkable career in surgery, research, and education, Moore has witnessed and contributed to some of the most important biomedical advances of the century, and his students now practice surgery worldwide. In this autobiography, he brings humor and warmth to the story of a lifetime at the forefront of medicine. In this fascinating book Moore describes his work in radioactive isotope research, burn therapy, breast cancer treatment, transplant science, and understanding the process of convalescence. Moore's colleagues have included such medical pioneers as George Thorn, David Hume, Thomas Starzl, John Gibbon, Steven Rosenberg, Harold Urey, and Nobel Prize winner Joseph Murray, and he recounts the setbacks and victories of their work. For example, he writes of the adventure he had with Charles Hufnagel in which 25 dogs, implanted with Hufnagel's experimental heart valves, made their escape into the Connecticut countryside and had to be recovered by dog control officers wielding stethoscopes. Yet Moore recalls with equal clarity the young mother who gave him a silver dollar for delivering her baby, the husband who begged that his ailing wife be allowed to die with dignity, and the desperately sick patients who made themselves available for experimental surgery and treatment. In one of his early operations he relieved "the pain, anguish, and threat to a wonderful small boy" by removing the boy's diseased appendix. He describes this capability as "a miracle and a privilege." The book includes a gripping account of the aftermath of the Cocoanut Grove nightclub fire in Boston in 1942, when Moore learned the horrific details of death by fire. He recounts both his experience with M.A.S.H. units and battalion aid stations in Korea and the sudden request from the U.S. State Department that resulted in his treating King Ibn Saud of Saudi Arabia. Moore's life story reflects his serious commitment to human well-being as well as his appreciation for the wonder of human life. Physicians, medical students, and all readers alike will find this book informative and inspirational. Francis Daniels Moore, M.D., is Moseley Professor of Surgery, Emeritus, Harvard Medical School and Surgeon-in-Chief, Emeritus, Peter Bent Brigham Hospital, Boston.
Keywords: Health and Medicine

Prudent Practices in the Laboratory: Handling and Disposal of Chemicals - National Research Council (The National Academies Press, 1995)
This volume updates and combines two National Academy Press bestsellers—Prudent Practices for Handling Hazardous Chemicals in Laboratories and Prudent Practices for Disposal of Chemicals from Laboratories—which have served for more than a decade as leading sources of chemical safety guidelines for the laboratory. Developed by experts from academia and industry, with specialties in such areas as chemical sciences, pollution prevention, and laboratory safety, Prudent Practices for Safety in Laboratories provides step-by-step planning procedures for handling, storage, and disposal of chemicals. The volume explores the current culture of laboratory safety and provides an updated guide to federal regulations. Organized around a recommended workflow protocol for experiments, the book offers prudent practices designed to promote safety and it includes practical information on assessing hazards, managing chemicals, disposing of wastes, and more. Prudent Practices for Safety in Laboratories is essential reading for people working with laboratory chemicals: research chemists, technicians, safety officers, chemistry educators, and students.
Keywords: Math, Chemistry, and Physics; Environment and Environmental Studies

Live Fire Testing of the F-22 - National Research Council (The National Academies Press, 1995)
The Live Fire Test Law mandates realistic survivability and lethality testing of covered systems or programs. A provision of the law permits the Secretary of Defense to waive tests if live fire testing would be "unreasonably expensive and impractical." Though no waiver was requested before the F-22 program entered engineering and manufacturing development, the Defense Department later asked that Congress enact legislation to permit a waiver to be granted retroactively. Rather than enact such legislation, Congress requested a study to explore the pros and cons of full-scale, full-up testing for the F-22 aircraft program. The book discusses the origin of testing requirements, evaluates the practicality, affordability, and cost-benefit of live fire tests, and examines the role of testing, modeling, and data bases in vulnerability assessment.
Keywords: Conflict and Security Issues; Space and Aeronautics

Recommendations for Research on the Health of Military Women: Bibliographies - Institute of Medicine (The National Academies Press, 1995)
Keywords: Health and Medicine

Expanding Metropolitan Highways: Implications for Air Quality and Energy Use -- Special Report 245 - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 1995)
TRB Special Report 245 - Expanding Metropolitan Highways: Implications for Air Quality and Energy Use reviews existing research on the links among highway capacity, traffic flow characteristics, travel demand, land use, vehicle emissions, air quality, and energy use in metropolitan areas; Identifies the conditions most likely to affect emissions and energy use; reviews the reliability of models and analyses that regional and state planning agencies use to forecast travel demand and land use, emission levels, and energy consumption; and recommends research strategies, modeling improvements, and data collection efforts to improve analytic capabilities.There are few more difficult or vexing local issues than the siting of a new highway or the expansion of an existing one. Local debates revolve around the trade-offs between easing congestion and increasing air pollution, noise, and sprawl. For many years, officials have attempted to respond to traffic congestion by adding highway capacity. Beyond meeting the public’s demand for roads, local and state officials view highway improvements as an integral part of their economic development strategies. Moreover, because vehicles in highly congested traffic operate inefficiently, it is believed that improving traffic flow would reduce emissions. On the other hand, opponents of new capacity contend that it induces more trips; that traffic in free-flow conditions also generates high emissions of some pollutants, particularly ozone precursors; and that the long-term effect of adding capacity is to support sprawling development. Examining these claims and counterclaims with technical evidence requires computer modeling of travel preferences, the resulting vehicle emissions, regional air quality, and the effects of new highway capacity on longterm land development.For decades, federal funding assistance created an incentive to build new highways. The Clean Air Act Amendments of 1990 represented an attempt to balance this incentive. Once these amendments became effective, metropolitan areas risked losing a share of their federal transportation funding if adding highway capacity would contribute to their failing to meet national air quality standards. Even though the regulations implementing the Clean Air Act Amendments require metropolitan areas to model the consequences of new capacity, the committee that conducted this study concluded that the existing analytical tools are inadequate for the task specified in the regulations. Whether new capacity is better or worse for air quality depends on local conditions. Relatively modest expansions probably have little effect, positive or negative, on air quality or land development in the urban periphery, whereas significant new capacity can, over a period of many years, contribute to increased travel, emissions, and low-density development patterns. Attempting to meet air quality goals through constraints on travel is an indirect policy measure. More direct benefits would accrue from improvements in vehicle technology, effective pricing or taxation of vehicle use, and more effective land development controls, although such measures are not without controversy and involve trade-offs of their own.
Keywords: Transportation and Infrastructure

The Development of Medications for the Treatment of Opiate and Cocaine Addictions: Issues for the Government and Private Sector - Institute of Medicine (The National Academies Press, 1995)
Pharmacotherapy, as a means of treating drug addiction in combination with other treatment modalities, has received too little attention from the research community, the pharmaceutical industry, public health officials, and the federal government. Medications to combat drug addiction could have an enormous impact on the medical consequences and socioeconomic problems associated with drug abuse, both for drug-dependent individuals and for American society as a whole. This book examines the current environment for and obstacles to the development of anti-addiction medications, specifically those for treating opiate and cocaine addictions, and proposes incentives for the pharmaceutical industry that would help overcome those obstacles and accelerate the development of anti-addiction medications.
Keywords: Health and Medicine

Environmental Medicine: Integrating a Missing Element into Medical Education - Institute of Medicine (The National Academies Press, 1995)
People are increasingly concerned about potential environmental health hazards and often ask their physicians questions such as: "Is the tap water safe to drink?" "Is it safe to live near power lines?" Unfortunately, physicians often lack the information and training related to environmental health risks needed to answer such questions. This book discusses six competency based learning objectives for all medical school students, discusses the relevance of environmental health to specific courses and clerkships, and demonstrates how to integrate environmental health into the curriculum through published case studies, some of which are included in one of the book's three appendices. Also included is a guide on where to obtain additional information for treatment, referral, and follow-up for diseases with possible environmental and/or occupational origins.
Keywords: Health and Medicine

Evaluation of the Army's Draft Assessment Criteria to Aid in the Selection of Alternative Technologies for Chemical Demilitarization (The National Academies Press, 1995)
Keywords: Environment and Environmental Studies

Improving the Environment: An Evaluation of the DOE's Environmental Management Program - National Research Council (The National Academies Press, 1995)
This book addresses remedial action and waste management problems that the DOE and the nation are now facing that are the result of 50 years of nuclear weapons development and testing—problems that require a reengineering of systems and a reexamination of the scientific, engineering, and institutional barriers to achieving cost-effective and safe stewardship of the nation's resources. Improving the Environment evaluates the DOE's environmental management program in four areas: regulatory measures, organization and management, priority-setting, timing and staging, and science and technology.
Keywords: Environment and Environmental Studies

Society's Choices: Social and Ethical Decision Making in Biomedicine - Institute of Medicine (The National Academies Press, 1995)
Breakthroughs in biomedicine often lead to new life-giving treatments but may also raise troubling, even life-and-death, quandaries. Society's Choices discusses ways for people to handle today's bioethics issues in the context of America's unique history and culture—and from the perspectives of various interest groups. The book explores how Americans have grappled with specific aspects of bioethics through commission deliberations, programs by organizations, and other mechanisms and identifies criteria for evaluating the outcomes of these efforts. The committee offers recommendations on the role of government and professional societies, the function of commissions and institutional review boards, and bioethics in health professional education and research. The volume includes a series of 12 superb background papers on public moral discourse, mechanisms for handling social and ethical dilemmas, and other specific areas of controversy by well-known experts Ronald Bayer, Martin Benjamin, Dan W. Brock, Baruch A. Brody, H. Alta Charo, Lawrence Gostin, Bradford H. Gray, Kathi E. Hanna, Elizabeth Heitman, Thomas Nagel, Steven Shapin, and Charles M. Swezey.
Keywords: Health and Medicine

Following the Money: U.S. Finance in the World Economy - National Research Council (The National Academies Press, 1995)
Many questions have been raised about America's status in the increasingly interconnected global economy. Yet key facts—such as the amount of foreign assets abroad owned by U.S. citizens—are not known. The crucial data needed to assess the U.S. position are unavailable. This volume explores significant shortcomings in U.S. data on international capital transactions and their implications for policymakers. The volume offers clearcut recommendations for U.S. agencies to bring data collection and analyses of the global economy into the twenty-first century. The volume explores:
Keywords: Industry and Labor

Tempo and Mode in Evolution: Genetics and Paleontology 50 Years After Simpson - Fitch, Walter M.; Ayala, Francisco J. (The National Academies Press, 1995)
Since George Gaylord Simpson published Tempo and Mode in Evolution in 1944, discoveries in paleontology and genetics have abounded. This volume brings together the findings and insights of today's leading experts in the study of evolution, including Ayala, W. Ford Doolittle, and Stephen Jay Gould. The volume examines early cellular evolution, explores changes in the tempo of evolution between the Precambrian and Phanerozoic periods, and reconstructs the Cambrian evolutionary burst. Long-neglected despite Darwin's interest in it, species extinction is discussed in detail. Although the absence of data kept Simpson from exploring human evolution in his book, the current volume covers morphological and genetic changes in human populations, contradicting the popular claim that all modern humans descend from a single woman. This book discusses the role of molecular clocks, the results of evolution in 12 populations of Escherichia coli propagated for 10,000 generations, a physical map of Drosophila chromosomes, and evidence for "hitchhiking" by mutations.
Keywords: Biology and Life Sciences

Regenerating Agriculture: Policies and Practice for Sustainability and Self-Reliance - Pretty, Jules N. (The National Academies Press, 1995)
It is becoming increasingly clear that a more sustainable agriculture can bring economic, environmental, and social benefits to farmers, communities, and nations. Regenerating Agriculture draws together for the first time new empirical evidence from a diverse range of agroecological and community settings to show the impacts of more sustainable practices. Twenty cases involving widespread success from Brazil, Burkina Faso, Honduras, India, Indonesia, Kenya, Lesotho, Mali, Mexico, Peru, Philippines, and Sri Lanka are presented, and are supported by field- and community-level data from more than 50 projects and programs in 28 countries. Despite this emerging evidence, many farmers still depend on high levels of external inputs. Regenerating Agriculture, identifies the common elements of successful programs and shows how those still using "modernist" approaches to agriculture can successfully turn to sustainable farming. The first chapter outlines the scale of the challenge and includes analysis of sustainable agriculture's characteristics and underlying philosophies and values. Pretty then presents analyses of the processes of agricultural modernization, focusing on both production- and conservation-oriented programs and policies and the common elements of success. Almost all of these successes have been achieved despite existing, biased policy environments that strongly favor "modern" approaches to agricultural development, and at the same time discriminate against sustainability. Regenerating Agriculture examines policy frameworks and institutional processes, then sets out 25 effective policies that are known to work to support the transition to greater sustainability and self-reliance in agriculture.
Keywords: Explore Science; Agriculture

The Advanced Materials and Processing Program and the Restructuring of Materials Science and Technology in the United States: From Research to Manufacturing (The National Academies Press, 1995)
Keywords: Engineering and Technology

Assessing the Social and Behavioral Science Base for HIV/AIDS Prevention and Intervention: Workshop Summary - Institute of Medicine (The National Academies Press, 1995)
Keywords: Health and Medicine

For the Public Good: Highlights from the Institute of Medicine, 1970-1995 - Institute of Medicine (The National Academies Press, 1995)
Keywords: Explore Science